MENERAPKAN KONSEP DASAR DALAM MEMBACA DENGAN METODE TUTOR SEBAYA DALAM RANGKA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV DI SDN 4 MONTONG BETOK TAHUN PELAJARAN 2020/2021 - Habibi, Muhamad Ridwan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
Applying Basic Concepts in Reading with the Peer Tutor Method in Order to Improve Reading Comprehension of Grade IV Students at SDN 4 Montong Betok for the 2020/2021 Academic Year. This study aims to determine student learning outcomes through the Peer Tutor Method, in learning Indonesian. This research was conducted in the form of Classroom Action Research. The stages carried out are: Action Planning, Action Implementation, Evaluation/Observation and Reflection. The subjects of this study were fourth grade students in the odd semester of the 2020/2021 academic year. as many as 29 people. The research data are: (1). Student learning outcomes are collected through learning outcomes tests. (2). Student activities were collected through observation guidelines. Data were analyzed descriptively qualitatively. From the results of data analysis, it was found that the increase in students’ reading ability can be seen from the increase in the average and completeness of student learning from cycle I to cycle II. In the first cycle the average score of students is 67.5 and in the second cycle the average value is 75.44, or it can be seen that the calculation of the percentage of classical completeness from the first cycle to the second cycle is 62% to 85%. Students who completed the first cycle were 21 students while those who did not complete were 13 (38%) people. But in the second cycle, 29 students (85%) completed and 5 students did not complete (15%). Based on the results of the data above, Peer Tutors can be used as a strategy in the learning process.